2022
DOI: 10.1177/21676968211051475
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Emerging Adulthood Related to the Impact of Childhood Bullying Victimization

Abstract: Findings from interviews with 15 emerging adults ( M age = 29.00, SD = .37) subjected to bullying victimization as children and suffering from poor psychological health in emerging adulthood revealed experiences of a very long duration of victimization, coping through adaptation to the bullying, and experiences of not receiving help from school personnel. Many participants described experiences of depression, anxiety, and even suicidal thoughts during the school-years victimization. They perceived several dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Our study also adds to the evidence about the salience of peer victimisation in childhood. Research has long established that being bullied in childhood is associated with both higher levels of inflammation and social problems in adulthood ( Lidberg et al, 2023 ; Takizawa et al, 2014 , 2015 ). The current study showed that peer victimisation, even when considered alongside other stressful life events at the level of both the child and the family, can produce such biological effects from childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also adds to the evidence about the salience of peer victimisation in childhood. Research has long established that being bullied in childhood is associated with both higher levels of inflammation and social problems in adulthood ( Lidberg et al, 2023 ; Takizawa et al, 2014 , 2015 ). The current study showed that peer victimisation, even when considered alongside other stressful life events at the level of both the child and the family, can produce such biological effects from childhood.…”
Section: Discussionmentioning
confidence: 99%
“…The participants in the present study, 10 men and five women ( M age = 29.13, SD = 0.52), were recruited from the research project MoS (Mobbning och Skola [Bullying and School]), an ongoing longitudinal study initiated in the year 2000 with a focus on bullying (see, for instance, Holmqvist Gattario, Lindwall & Frisén, 2019; Lidberg, Berne & Frisén, 2022). Purposive sampling was applied (Schwab & Syed, 2015) in a process using data from the participants' previous participation in the MoS study.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, qualitative research has indicated that negative long‐term outcomes of being bullied in school can impact the developmental features of emerging adulthood (Lidberg, Berne & Frisén, 2022). However, to our knowledge, resilience in relation to long‐term outcomes of being bullied in school has not been investigated with regard to the developmental period of emerging adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Notable, the majority of bullying victimization‐related outcomes research was conducted in the sample of childhood and adolescence (e.g., see Moore et al., 2017; Walters & Espelage, 2018; Zhu et al., 2021), paucity of research investigated the emerging adults. Emerging adulthood, spanning from ages 18–25, represents a unique developmental stage between adolescence and young adulthood, characterised by increased instability and uncertainty (Arnett et al., 2014; Lidberg et al., 2022). Recently, studies have found associations between bullying victimization and subsequent maladjustment, such as self‐injurious and suicidal behaviour, in this age group (Zhu et al., 2021, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…uncertainty (Arnett et al, 2014;Lidberg et al, 2022). Recently, studies have found associations between bullying victimization and subsequent maladjustment, such as self-injurious and suicidal behaviour, in this age group (Zhu et al, 2021(Zhu et al, , 2022.…”
mentioning
confidence: 97%